Economic impact of fetal wastage and common diseases, along with their incidence rates and seasonal variations, at an abattoir in FCT, Nigeria - Ibrahim Dauda Dauda; Abdulhakeem Binhambali; Abdurrahman Hassan Jibril; Zainab Oyiza Idris; Farhan Rhidor Akorede (PLoS ONE, 2025)
Infectious diseases and fetal wastage (FW) present major challenges in livestock management, particularly in sub-Saharan Africa, including Nigeria. This study assessed the season variations, incidence rate and economic impact of prevalent diseases and FW at the Kubwa (KB) abattoir in the Federal Capital Territory (FCT) of Abuja, Nigeria. Over a year-long period (January to December 2023), we analyzed 5,779 cattle through daily post-mortem inspections. Disease identification was based on morphological and gross lesions characteristic of the conditions studied. Economic losses from condemned organs and FW were calculated using the formula TEL = N × P × W. The results indicated statistically significant seasonal variations in the incidence of Fasciolosis (FS), Paramphistomosis (PP), and FW, with p-values of 2.52x10^-10, 3.33x10^-9, and 0.003, respectively. In contrast, Tuberculosis (TB), Contagious Bovine Pleuropneumonia (CBPP), Dermatophilosis (DM), Abscess (AB), and Moneziasis (MZ) did not show significant seasonal variation. The total economic impact of condemned organs and FW was 104,348 USD (equivalent to 99,130,600 NGN at the time of the study), representing a considerable threat to food security and substantial economic losses for farmers. Considering the zoonotic potential of some diseases, which can be transmitted to those handling the carcasses, there is a critical need for enhanced inspection protocols, continuous disease surveillance, and timely reporting in slaughterhouses. The notable economic losses from condemned organs also underscore the necessity of implementing pregnancy tests for female animals before slaughter to protect food security and support the nation’s economy. These findings highlight the essential role of abattoirs in improving food security, detecting zoonotic diseases, and bolstering public health and economic stability in low-income countries.